The effects of note-taking methods on lasting learning: the role of motivation and cognitive load - Yıldırım, Mesut (Frontiers in Psychology, 2026)
IntroductionThis randomized controlled experimental study examined the effects of four note-taking methods (Cornell, Parallel, Digital, and Sentence) on lasting learning (retention) in primary-level teacher candidates, while also exploring the roles of learning motivation and cognitive load.MethodsA total of 134 participants were randomly assigned to three experimental groups (Cornell, Parallel, Digital) and one control group (Sentence). Following a one-session orientation, the intervention spanned 5 weeks (2 h/week). Measures included a researcher-developed Academic Achievement Test (pre-, post-, retention), a validated Learning Motivation Scale (pre-, post-), and a single-item cognitive load rating collected after each lesson. Analyses used mixed ANCOVA with Bonferroni-corrected post-hoc tests and regression analyses.ResultsMixed ANCOVA revealed significant main effects of time and group, whereas the time × group interaction was not significant. Post-hoc tests showed no significant pairwise differences at post-test; at retention, only the Cornell group scored significantly higher than the Sentence group. Motivation increased significantly in the Cornell and Parallel groups, while Digital and Sentence showed no significant pre–post change. Cognitive load differed by method, with Digital reporting significantly lower load than Parallel and Sentence. Regression analyses indicated that motivation was significantly associated with retention, whereas cognitive load was not.ConclusionsOverall, retention differences were limited and observed only for the Cornell–Sentence comparison. Learning motivation showed the most consistent association with retention scores, whereas cognitive load showed no significant association with retention in the regression analyses.